2013
DOI: 10.1186/1477-7525-11-46
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and life satisfaction in colorectal cancer survivors: trajectories of adjustment

Abstract: BackgroundThis longitudinal study describes the five year trajectories of health-related quality of life (HR-QOL) and life satisfaction in long term colorectal cancer survivors.Patients and methodsA population-based sample of 1966 colorectal cancer survivors were surveyed at six time points from five months to five years post-diagnosis. Predictor variables were: socio-demographic variables, optimism; cancer threat appraisal; perceived social support. Quality of life was assessed with the Functional Assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
84
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 36 publications
13
84
1
2
Order By: Relevance
“…In 3 studies (2 longitudinal), less perceived social support and worse social network measures (e.g., fewer social contacts) were found to be associated with lower HRQoL reported by CRC survivors 5 or more years postdiagnosis [35,47,70]. Regarding socioeconomic factors, 2 longitudinal studies in CRC survivors observed significantly lower HRQoL 2-5 years postdiagnosis among survivors who did not have private health insurance at 5-6 months postdiagnosis [31,35].…”
Section: Environmental Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 3 studies (2 longitudinal), less perceived social support and worse social network measures (e.g., fewer social contacts) were found to be associated with lower HRQoL reported by CRC survivors 5 or more years postdiagnosis [35,47,70]. Regarding socioeconomic factors, 2 longitudinal studies in CRC survivors observed significantly lower HRQoL 2-5 years postdiagnosis among survivors who did not have private health insurance at 5-6 months postdiagnosis [31,35].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Evidence was graded inconsistent for tumor stage and localization. Either associations of higher tumor stage with lower HRQoL were observed [29,33,35,40,42,43,47,48] or there was no significant association between tumor stage and HRQoL [32,39,41,[49][50][51]. Similarly, studies observed either no significant association between tumor localization and HRQoL [29,32,42,51] or that rectal cancer survivors reported lower HRQoL than colon cancer survivors [35,48].…”
Section: Health Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…The different aspects of HRQOL are parts of the well-being of every person and influence a person's health status 9 . HRQOL can be predicted by a number of variables.…”
Section: Introductionmentioning
confidence: 99%